Peran Kepemimpinan Lurah Dalam Meningkatkan Kesadaran Masyarakat (Studi Pada Kelurahan Jati Mekar Kecamatan Kendari Kota Kendari) - Apriani, Apriani; Kadir, Abdul; Basri, Muhammad (Universitas Halu Oleo, 2021)
This study aims to determine the leadership role of the Village Head in increasing public awareness to build a clean, beautiful and orderly environment (study in Jati Mekar Village, Kendari District, Kendari City). This type of research is descriptive qualitative. Data collection techniques were carried out by means of librarian studies, literature studies, and field research, using interview methods and documentation methods. The results of this study indicate that: the implementation of the function of the leadership role of the village head in increasing public awareness to build a clean, beautiful and orderly environment has not been implemented as a whole or comprehensively and must be considered significantly. We can find all of that in the environmental conditions in Jati Mekar Village.